Young Children’s Development of Fairness Preference - Li, Jing; Wang, Wen; Yu, Jing; Zhu, Liqi (Frontiers in Psychology, 2016)
Fairness is one of the most important foundations of morality and may have played a key role in the evolution of cooperation in humans. As an important type of fairness concern, inequity aversion is the preference for fairness and the resistance to inequitable outcomes. To examine the early development of fairness preference in young children, sixty 2- and 3-year-old children were recruited to examine young children’s preferences for fairness using a forced choice paradigm. We tested how toddlers acted when they took charge of distributing resources (two candies) to themselves and others and when they were the recipients of both other-advantageous distribution and self-advantageous distribution. Different alternative options were paired with the same fair option in the two conditions. In the other-advantageous condition, children had fewer resources in the alternative options than others, whereas their resources in the alternative options were greater than others’ in the self-advantageous condition. The results showed that more children displayed fairness preferences when they distributed resources between two friends than when they distributed resources between a friend and themselves. In both scenarios, three-year-old children were more likely to demonstrate fairness than 2-year-old children. The findings suggest that inequity aversion develops in young children and increases with age over the course of early childhood. When they were recipients, there was a trend in young children’s preference for fairness in the other-advantageous condition compared with the self-advantageous condition. This suggests that children might tend to be more likely to display inequity aversion when they are in a disadvantageous position.